Analysis on Management's Managerial Competence and Its Influence on Pos-PAUD Service Quality - Wahyuni, Sri; Sumarsono, Raden Bambang; Desyanty, Ellyn Sugeng; Asimiran, Soaib bin (Journal of Nonformal Education, 2021)
Pos-PAUD is one form of non-formal PAUD unit as the development of Integrated Services Post (Posyandu) activities. Previous researches results state that Pos-PAUD service quality is far from what is expected since the village society-built institution has many limitations. Its managements academic qualification and competence is not required as demanded by the law. This research aims at mapping Pos-PAUD managements managerial competence and its influence on its institutional service quality. The research was conducted with a correlational quantitative research design. The research population was the Pos-PAUD management in Malang City of about 156 people. The research samples were 65 people determined based on the proportional random sampling technique. The data were collected using a questionnaire technique. The questionnaire validity was tested using Pearsons Product Moment technique, while questionnaire reliability was tested using Cronbachs Alpha technique. The data were analyzed using descriptive analysis and regressive analysis techniques using SPPSS 23.00 for windows. The result of descriptive analysis shows that managements managerial competence and institutional service quality are not maximal yet since there is unmet indicator. The hypothesis test result shows that Fcount is 162.407 (Sig F = 0.000). Ftable at significance level 5% is 3.14. Since Fcount Ftable (162.407 3.14) and Sig F 5% (0.000 0.05) thus Ho is rejected, which means that managements managerial competence significantly influences Pos-PAUD service quality. This research result may be taken as the base to design Pos-PAUD managements competence building activity that is currently seldom performed and as the base of development of Pos-PAUD service quality improvement model.